Direct Current Electric Teaching Materials Through Google Classroom for 16-17 Years Old Students: Teacher Perception - Yani, Arlin Dwi; Wati, Mustika; Misbah, Misbah (CV FOUNDAE, 2021)
The research aims to produce direct current electricity teaching materials and their application through Google Classroom for students in vocational high schools. This research uses 4-D model development (Define, Design, Develop, and Disseminate). The resulting teaching materials were analyzed for their validity and practicality. This product was distributed to 50 physics teachers. The data were obtained through a validation sheet of teaching materials and a teacher's perception questionnaire on the practicality of teaching materials. The results showed that: (1) the teaching materials developed were valid because the validity of the lesson plans, worksheets, assessments, and teaching materials was in the valid category; and (2) practicality seen from the results of teachers' perceptions of lesson plans in the practical category, and the results of teachers' perceptions of worksheets, assessments, and teaching materials in the very practical category. So it can be concluded that the development of direct current electricity teaching materials using the Google Classroom application is valid and practical for use in learning physics